EFFECT OF THE ETHICAL CLIMATE ON EMPLOYEE ENGAGEMENT THROUGH WORK SATISFACTION AS AN INTERVENING VARIABLES (Case Study on Bank Jatim Syariah Malang) - Titiek Ambarwati; R. Iqbal Robbie (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Employee engagement has a very close relationship with the competitive advantage of an organization or company, where this competitive advantage cannot be achieved if there is no employee engagement with the company. Employee engagement is a form of positive employee attitudes towards their work and organization which is characterized by feelings of vigor, dedication and absorption. This study resulted in an ethical climate on employee engagement that had a significant positive effect, the effect of ethical climate on satisfaction was also positive, and satisfaction was able to mediate the relationship between ethical climate and employee engagement on employees of Bank Jatim Syariah Malang City. Keywords: ethical climate, employee engagement, satisfaction